Feasibility of E-Magazine Media Submaterial Fungi Diversity Inventory Results in the Padang Tikar Protected Forest, Kubu Raya Regency - Ariswandi, Ariswandi; Yeni, Laili Fitri; Fajri, Hayatul (PendIPA Journal of Science Education, 2025)
Learning media aims to improve the quality of teaching and learning and motivate students through engaging presentations. This study aimed to determine the feasibility of e-magazine media from the macroscopic fungi inventory in Padang Tikar Protection Forest, Kubu Raya Regency. The development of e-magazine media was carried out to become an additional information source on the fungi diversity submaterial. This study used a qualitative descriptive method of 2-stage research, including interviews and media making. The media-making stage was then divided into pre-production, production, and post-production. Media feasibility validation was carried out at the post-production stage with a Likert scale assessment and analyzed using Lawshe's formula. The media validation results obtained a CVI value of 1.00. The validation results exceeded the value of 0.99 criteria from 5 validators; it can be concluded that the e-magazine media is valid for use in the fungi diversity submaterial.